Effectiveness of poly-γ-glutamic acid in maintaining enamel integrity - Qamar, Zeeshan; Rahim, Zubaidah Haji Abdul; Gan, Seng Neon; Chew, Hooi Pin; Zeeshan, Tayyaba (Elsevier, 2019)
Objective: The aim of the study was to determine demineralisation inhibition and remineralisation potential of poly-γ-glutamic acid with its possible mechanism of action on human dental enamel. Methodology: Three sodium-fluoride(NaF) concentration(0.01%w/v,0.1%w/v and 0.5%w/v respectively)and two poly-γ-glutamic acid(PGGA)concentration(1%w/v and 2%w/v respectively)were prepared in 0.1 M acetic acid(pH4.0)and deionized distilled water.For de/re-mineralisation study, tooth samples (18 teeth varnished, leaving a 2 mm2 window on the mid-buccal surfaces) were immersed in respective acidified NaF and PGGA solutions. The Ca2+ release/uptake was monitored with ISE over 72-hr with increasing pH every 24-h from 4.0 to 6.0.These teeth were later subjected to cross-sectional microhardness to determine integrated mineral recovery of enamel on increasing pH of respective acidified solution.In order to determine mechanism of PGGA,two concentrations of PGGA in deionized-water-solutions were used for tooth samples immersion followed by overnight drying then later subjected to Fourier Transform Infra-Red(FT-IR) analysis.The FT-IR analysis was also carried out on PGGA powder.For control,the experiment was repeated using hydroxyapatite(HAp)pellets.The density of PGGA solutions(1%and2%)was also measured to determine their dynamic viscosities. Results: The ISE and microhardness testing revealed statistically significant (ρ ≤ 0.05) dissolution inhibition and remineralisation potential for tooth sample treated with acidified 2%PGGA. From the FT-IR spectra, it was observed that the profiles of the enamel and HAp surfaces treated with 1%-and 2%-PGGA solutions were similar to those of PGGA powder.It was found that the viscosity of PGGA increases with increasing concentration. Conclusion: The study implies that 2% PGGA is more effective than NaF as forms a coating layer to protect from demineralisation and promote remineralisation of the tooth surface. © 2019 Elsevier Ltd